The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5483/bmbrep.2012.45.3.147
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative modification of ferritin induced by methylglyoxal

Abstract: Methylglyoxal (MG) was identified as an intermediate in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Studies have shown that ferritin can act as an acute phase reactant; also, ferritin has been linked to certain metabolic diseases and their components [2,3,20]. The latter assumption has been derived only from statistical correlations, with the mechanisms through which ferritin participates in such disorders remaining unclear [3,21]. On the other hand, it has been shown that ferritin can undergo oxidative damage by carbonyl compounds, such as methylglyoxal or ROS, which have been related to the increase in the iron content of cells that can be deleterious to cells [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that ferritin can act as an acute phase reactant; also, ferritin has been linked to certain metabolic diseases and their components [2,3,20]. The latter assumption has been derived only from statistical correlations, with the mechanisms through which ferritin participates in such disorders remaining unclear [3,21]. On the other hand, it has been shown that ferritin can undergo oxidative damage by carbonyl compounds, such as methylglyoxal or ROS, which have been related to the increase in the iron content of cells that can be deleterious to cells [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The latter assumption has been derived only from statistical correlations, with the mechanisms through which ferritin participates in such disorders remaining unclear [3,21]. On the other hand, it has been shown that ferritin can undergo oxidative damage by carbonyl compounds, such as methylglyoxal or ROS, which have been related to the increase in the iron content of cells that can be deleterious to cells [21,22]. Advanced glycation end-products (AGEs) are a diverse group of highly oxidant compounds with pathogenic significance in diabetes as well as in several other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have also reported that the modification of ferritin, iron containing protein, was induced by MG (16). To further examine whether the modification of ferritin causes DNA damage, we exposed the plasmid pUC19 to the ferritin/MG/lysine system.…”
Section: Resultsmentioning
confidence: 99%
“…Since acid hydrolysis destroys tryptophan, the tryptophan content of oxidized and native Cu,Zn-SOD preparations was determined by means of alkaline hydrolysis as described previously (43). The amino acid content of acid and alkaline hydrolysates was determined by HPLC separation of their phenylisothiocyanate derivatives by using a Pico-tag free amino acid analysis column and a 996 photodiode array detector (Waters, USA).…”
Section: Methodsmentioning
confidence: 99%